Absolute cost difference and persistent trade imbalances : the harrodian adjustment process - Shaikh, Anwar (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
The classical economists understood that international trade is conducted by profit-seeking export and import firms, not «nations». For instance, in his discussion of foreign trade Smith emphasizes that «private profit is the sole motive which determines the owner of any capital to employ it either in agriculture, in manufactures, or in some particular branch of the wholesale or retail trade» (Smith, 1973, p. 474). The classicals also emphasized that in any given industry, competition favors lower-cost firms because they are better able to lower prices and damage their higher-cost competitors. Smith extends this principle to the analysis of international trade, which implies that capitals located in nations with lower costs are likely to be more successful in the international arena (1973, p. 35). In other words, absolute cost advantage1 applies equally well to competition within a nation as it does to competition between nations
Páginas 51-58
Keywords: Comercio internacional; Teoría económica; https://purl.org/pe-repo/ocde/ford#5.02.01